Using bioinformatic tools to mitigate vector-borne disease - Bird, Edward John (My University, 2025)
Vector-borne diseases pose significant threats to both livestock and human health, yet our understanding of vector-pathogen interactions remains limited in certain systems due to inadequate genomic resources and surveillance methodologies. This dissertation addresses these gaps through integrated genomic, transcriptomic, and metagenomic approaches applied to veterinary and medically important arthropod vectors. We present a chromosome-scale genome assembly of Culicoides sonorensis, a North American vector of several livestock diseases, including bluetongue virus. Using third-generation sequencing technologies, we assembled three chromosomes representing 99.4% of the nuclear genome, with comprehensive gene annotations based on RNA-seq data from each life stage. Comparative genomics revealed that Culicoides represent a unique clade of hematophagous vectors and identified lineage-specific gene expansions. We then leveraged this genomic resource to examine transcriptomic responses of C. sonorensis to bluetongue virus serotype 17 (BTV-17) and vesicular stomatitis New Jersey virus (VSNJV) infections. Differential expression analysis revealed distinct virus-specific responses, with BTV-17 eliciting a stronger transcriptional response than VSNJV. Pathway analysis showed that genes associated with abnormal behavior were differentially expressed in response to BTV-17 infection, as well as components of the innate immune system, in response to both BTV-17 and VSNJV. This analysis also identified several genes that may play crucial roles in vector competence. Lastly, we utilized these genomic analysis technologies to develop a xenosurveillance framework using house flies (Musca domestica) as bioindicators for environmental antimicrobial resistance and pathogen monitoring, demonstrating location-specific resistome profiles between urban and rural environments. Together, these advances provide essential genomic foundations for vector biology research, reveal novel insights into vector-pathogen interactions, and establish scalable surveillance methodologies for monitoring emerging threats in diverse environmental contexts.
Keywords: Genomics; Entomology; Vector